Comparison of Antibody Responses against Two Molecules from Ascaris lumbricoides: The Allergen Asc l 5 and the Immunomodulatory Protein Al-CPI - Velky Ahumada; Josefina Zakzuk; Lorenz Aglas; Sandra Coronado; Peter Briza; Ronald Regino; Fátima Ferreira; Luis Caraballo (Biology, 2023)
Immunity to Ascaris lumbricoides influences the pathogenesis of allergic diseases. Antibody responses to its proteins have been found to be associated with asthma presentation; however, helminth products that induce immunosuppression have been reported, which also raise specific antibodies. We aimed to evaluate antibody responses (IgE, IgG4 and IgG) to two A. lumbricoides molecules, Asc l 5 and Al-CPI (an anti-inflammatory Cysteine Protease Inhibitor), in an endemic population, exploring their relationships with the infection and asthma. The two molecules were produced as recombinant proteins in E. coli expression systems. Specific antibodies were detected by ELISA. Lower human IgE, but higher IgG4 and IgG antibody levels were observed for Al-CPI than for rAsc l 5. The IgE/IgG4 isotype ratio was significantly higher for Asc l 5 than for Al-CPI. In humans Al-CPI did not induce basophil activation as has been previously described for Asc l 5. In mice, Al-CPI induced fewer IgE responses, but more IgG2a antibody titers than rAsc l 5. Our results suggest that these molecules elicit different patterns of immune response to A. lumbricoides.